ECONOMIC EFFICIENCY REGARDING CASTOR BEAN (Ricinus communis L.) CULTIVATION IN PEDOCLIMATIC CONDITIONS IN THE CENTER OF MOLDOVA, ROMANIA - Bogdan MÎRZAN; Oana MÎRZAN; Margareta NAIE; Constantin LUNGOCI; Elena STAVARACHE; Mihai STAVARACHE; Diana BATÎR RUSU; Alexandra Andreea BUBURUZ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In Romania, castor bean (Ricinus communis L.) is not cultivated on large areas, offering beneficial perspectives to those who want to set up a business in the agricultural field. The expansion of surfaces with this species is limited by climatic conditions, and in particular by the fall of early autumn broths, which can compromise the entire production of secondary colds. Climate change in recent years has led to the expansion of the castor cultivation area, which has obtained satisfactory production in the central area of Moldova if all technological links are respected. The research aimed to identify the genotype with the highest adaptability to the pedoclimatic conditions in the area of influence in order to establish the optimal sowing age and the distance between rows on the production and quality of seeds, implicitly in obtaining a net profit. The results obtained from 20 8-2020 showed that the best option of cultivation and obtaining high net profit for the pedoclimatic conditions in the center of Moldova is the one for the variety Teleorman sown in second age and 70 cm distance between rows ( 2,046 lei·ha- for a production of ,607 Mg·ha- ).